Cell Dynamics: Mechanisms, Technologies, and Applications in Health and Disease - Akram, Muhammad; Umaru, Isaac John; Mahmood, Abid; Hasan, Mohammed Khudhair; Abdulghafoor, Hind A.; Khan, Fahad Said; Ozdemir, Fethi Ahmet; Sołowski, Gaweł; Ali, Jaouher Ben; Al-Musawi, Jehan Mohammad (African Journal of Biochemistry and Molecular Biology Research, 2025)
The intricate and well-coordinated activities of cells in response to both internal and external stimuli are referred to as cell dynamics. These behaviors help living things grow, differentiate, maintain, and adapt. Using a variety of interdisciplinary techniques from molecular biology, biophysics, computational modeling, and live-cell imaging, this field examines the dynamic processes that control cell morphology, intracellular transport, cytoskeletal reorganization, signal transduction, and cell motility. The capacity of cells to alter their structure and function in real time, allowing for quick reactions to changes in the environment, damage, or developmental signals, is a key component of cell dynamics. The complex coordination of cytoskeletal filaments, vesicle trafficking channels, and signaling networks that underpin activities including mitosis, migration, immunological surveillance, and synaptic plasticity has been made visible by developments in high-resolution imaging and single-cell analysis. Recent research has demonstrated that cellular activities incorporate stochastic fluctuations, spatial compartmentalization, and emergent features resulting from the combined actions of molecular complexes, in addition to deterministic biochemical routes. It has been demonstrated that the mechanical characteristics of the cellular microenvironment, such as the extracellular matrix composition and substrate stiffness, are essential for regulating dynamic cellular responses, especially during wound healing, tissue formation, and cancer progression. Additionally, the enormous datasets produced by live-cell imaging and omics technologies are being decoded more and more using computational models and artificial intelligence tools, which offer fresh perspectives on the temporal and spatial control of cellular activities. In addition to expanding our understanding of basic cell biology, an understanding of cellular dynamics may help develop therapeutic approaches that target dysregulated cellular activities in conditions including cancer, dementia, and immunological disorders. In order to anticipate cellular outcomes and manipulate cell destiny for applications in synthetic biology and regenerative medicine, it will be crucial to combine quantitative modeling with experimental data as we continue to clarify the fundamentals of cellular structure and adaptability.